Living Qur’an Dan Hadis Di Tk Syarif Ar-Rasyid Islamic School Medan (Studi Tentang Internalisasi Akhlak) - Sitorus, Masganti; Sumanti, Solihah Titin; Gusman, Media (Lembaga Penelitian dan Pengabdian kepada Masyarakat (Center for Research and Community Services), Universitas Islam Negeri Sultan Aji Muhammad Idris Samarinda, 2021)
This study aims to analyze the readiness of children in efforts to internalize morals through the Living Qur'an and Hadith, efforts to internalize morals by teachers through the living Qur'an and Hadith, parental participation in efforts to internalize morals through living. This research was conducted at TK Syarif Ar-Rasyid Islamic School Medan. The research method used is qualitative using a phenomenological approach. Data collection techniques used interviews, observations, and documentation studies. Data analysis uses data reduction, data display, and drawing conclusions. The results showed that Syarif Ar-Rasyid Islamic School Medan Kindergarten students were prepared to accept the process of moral internalization through living Qur'an and Hadith activities. This is evident from the physical and psychological readiness possessed by students. (2) Efforts to internalize morals are carried out in two forms, namely integrated with learning, and outside learning. There are four steps of moral internalization, namely moral determination, practice, habituation, and natural appearance. The media used are posters, MP3 Murotal short suras. The evaluation of moral internalization uses the technique of observing children's developmental achievements. (3) Parental participation is carried out through controlling children's development, supporting and facilitating children's activities, semester meeting activities, getting used to the same attitude at home, participating in parenting recitations. Keywords: Internalization of Akhlak, Living Qur'an and Hadith, Early Childhood